PERBANDINGAN EFEKTIVITAS TRAGAKAN DAN PVP SEBAGAI PENGIKAT TERHADAP SIFAT FISIK TABLET HISAP EKSTRAK JAHE (Zingiber officinale Roxb.) - Wintari Taurina; Melinda Dewi M; Yandi Syukri; Asih Triastuti (Universitas Islam Indonesia, 2005)
ABSTRACTGinger (Zingiber Officinale Roxb) is a traditional plants usually used to relieve pain, rheumatism,and neutralize poison. The aim of this study was to get the optimum concentration of tragacanthand PVP as a binding agent in ginger lozenges formulation. The components from ginger wereextracted using percolation with ethanol 70% and then evaporated using rotary evaporator.Lozenges were made in three formulas ; formula 1 (5%), 2 (7,5%), 3 (10%) of tragacanth and PVPusing wet granulation method. Granules and tablets were tested for its physical properties, andanalyzed using Pearson correlation. The result showed that, all of three formulas were good,comply with a regulation of physical properties and disolution time in the mouth. Variation oftragacanth and PVP concentration affected physical properties of tablets. It showed that the greaterconcentration of tragacanth and PVP, the larger the hardness and the longer the disolution time oftablets. The third formula (tragacanth 10% b/v) gave an optimum physical properties and solubletime of tablets, with weight variety deviation 0,98%, hardness 10,18 kg, friability 0.11% anddisolution time 11.50 minutes. The three formulas were received by respondens withprerequirement of improving sweetness, repairing form and the color of tablets.Key words :Ginger lozenges, tragacanth, PVP, wet granulation method.